A quantitative approach to the cranial ontogeny of the puma - Giannini, Norberto Pedro (2010)
The cranial ontogeny of specialized mammals is relevant to the understanding of the connection of form and function in a developmental, ecological, and evolutionary context. As highly specialized carnivores, felids are of especial interest. We studied the postnatal ontogeny of the skull in Puma concolor (Mammalia: Carnivora: Felidae) using a quantitative approach. We interpreted our results in the light of a previous qualitative assessment of ontogenetic changes in the species. This represents one of the few integrative studies of skull development in any extant species of wild felids. We report patterns of multivariate allometry of 19 linear skull dimensions measured in 48 Argentine specimens. We examined the (jackknife resampled) departures from isometry as well as the interplay of isometric and allometric trends in shaping the puma skull. Both the qualitative and quantitative results indicate that the major ontogenetic changes are directly linked to cranial structures that support a developing masticatory apparatus and its associated jaw and neck musculature, which are essential for the action of canines and carnassials during the killing bite and slicing flesh. Sexual differences suggest allometric scaling (hypo- or hyper-morphosis) as key processes in the development of the puma skull.